KEDUDUKAN KEJAKSAAN DAN PENGISIAN JABATAN JAKSA AGUNG DALAM SISTEM KETATANEGARAAN INDONESIA - Husaini, Husin; Askar, Muhammad Afdhal (Bertuah: Jurnal Syariah dan Ekonomi Islam, 2020)
ABSTRACTThe Attorney General's Office of the Republic of Indonesia is a government institution that exercises state power in the field of prosecution and other powers based on law. Attorney General who is the leader and highest person in charge of the prosecutor's office who leads, controls the implementation of the duties and authorities of the prosecutor's office. As a law enforcement agency under the executive power and the position of Attorney General who is appointed, dismissed, and accountable to the President, this state institution is not independent in exercising its authority. This research uses normative legal research. The source of the data used in this thesis is collection through literature research, namely by examining secondary data in the form of books, laws and regulations, papers related to this writing. The results of this study conclude that the public prosecutor's office is in the executive realm to make this institution easy for executive power to intervene. Based on this research, the Attorney General's Office exercises authority related to judicial power, but this institution enters the executive realm and filling the position of Attorney General is the President's prerogative. Therefore, the authors recommend changes to the position of the Attorney General's Office and filling the position of Attorney General with changes to the constitution or changes to the prosecutor's law. This is to create an independent prosecutor's office in exercising its authority free from influence and interference from any power. Keywords: Position and Position, Attorney General's Office and Attorney General, Independent. ABSTRAKKejaksaan Agung Republik Indonesia adalah lembaga pemerintah yang menyelenggarakan kekuasaan negara di bidang penuntutan dan kewenangan lain berdasarkan undang-undang. Jaksa Agung yang merupakan pimpinan dan penagung jawab tertinggi kejaksaan yang memimpin, mengendalikan pelaksanaan tugas dan wewenang kejaksaan. Sebagai lembaga penegak hukum yang berada di bawah kekuasaan eksekutif dan jabatan Jaksa Agung yang diangkat, diberhentikan, dan bertanggung jawab kepada Presiden, lembaga negara ini tidak independen dalam menjalankan kewenangannya. Penelitian ini menggunakan jenis penelitian hukum normatif. Sumber data yang digunakan dalam jurnal ini adalah pengumpulan melalui penelitian kepustakaan yaitu dengan menelaah data sekunder berupa buku-buku, peraturan perundang-undangan, makalah yang berkaitan dengan penulisan ini. Hasil penelitian ini menyimpulkan bahwa kejaksaan berada pada ranah eksekutif sehingga memudahkan lembaga eksekutif untuk mengintervensi. Berdasarkan hasil penelitian ini, Kejaksaan Agung menjalankan kewenangan terkait kekuasaan kehakiman, namun lembaga ini masuk ke ranah eksekutif dan pengisian Jaksa Agung merupakan hak prerogatif Presiden. Oleh karena itu, penulis merekomendasikan perubahan kedudukan Kejaksaan Agung dan pengisian jabatan Jaksa Agung dengan perubahan konstitusi atau perubahan hukum kejaksaan. Kata Kunci: Kedudukan dan Pengisian Jabatan, Kejaksaan dan Jaksa Agung, Independen.